Plasmonic hot electron induced layer dependent anomalous Fröhlich interaction in InSe - Mahfujur Rahaman (Nature Portfolio, 2021)
Electron-phonon coupling plays a central role in a variety of low dimensional structures. The authors unveiled the subtle interaction between optical phonons and charge carriers by applying Raman spectroscopy to plasmonic nanostructures fabricated on atomically thin InSe. These findings provide insights to develop future high-performance nanoelectronic devices.